Research on enterprise risk management and chief risk officers - Pagach, Donald (Henry Stewart Talks, 2014)
Characteristics of firms adopting enterprise risk management, ERM, Chief Risk Officers, Market reaction to firms implementing enterprise risk management, Cumulative abnormal returns, Stock return volatility, Earnings volatility, Growth options, Firm performance and adoption of enterprise risk management, Return on assets